(untitled) (E Conference Zone, 2022)
The article identifies the possibility of using specialized software tools such as Mathcad, Matlab, Mapl, Matematica in the study of algebraic materials, as well as a decision-making skills that are formed in the student in the context of applied mathematics teaching using information and communication technologies.